Clinical correlates of noise sensitivity in patients with acute TBI. (3rd July 2019) - Shepherd, Daniel; Landon, Jason; Kalloor, Mathew; Theadom, Alice
ABSTRACT: Primary objective : The impact of noise sensitivity (NS) on the daily functioning of people who have experienced a traumatic brain injury (mTBI) is an understudied area, particularly following mTBI. The primary objective of this cross-sectional study was to investigate clinical markers of NS in a sample of New Zealand adults following mTBI. Research design : Cross-sectional study. Methods and procedures : A community-based sample of 151 adults who had experienced a brain injury in the last two weeks completed assessments estimating cognitive functioning, postconcussion symptoms (including NS), and affective state. Results : Over half the sample (59%) reported some degree of NS. Exploratory statistical analyses indicated that NS was associated with being female, living in a rural area, number of previous brain injuries, cognitive flexibility scores, reaction time, perceptions of recovery, anxiety, and depression. Regression analyses revealed that anxiety was the dominant correlate of NS (B = .120, p < .001, 95% CI [0.069, 1.71]). Conclusions : As the first study to explore the correlates of NS following mild TBI, the findings have important clinical and research implications. The present findings suggest that treatment approaches targeting anxiety may be effective in reducing NS in people who have experienced a brain injury. Moreover, evidence is presented suggesting that NS is unlikely to reflect malingering, and should be treated as a genuine somatic symptom of brain injury.